TINGKAT PENGETAHUAN PENGGUNAAN OBAT BEBAS DAN OBAT BEBAS TERBATAS UNTUK SWAMEDIKASI PADA MASYARAKAT RW 8 MOROBANGUN JOGOTIRTO BERBAH SLEMAN YOGYAKARTA - Ana Hidayati; Haafizah Dania; Murtyk Dyahajeng Puspitasari (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2017)
Currently, there are developed illnesses that encourage humans to do their own alternative medication. In 2002, an estimated shows that 92% of people in the world choose the alternative medication namely self medication, by using over the counter medicine including free and limited, however the level of knowledge in using this medication is still poor, then it is possible to make a mistake. Therefore, this research aims to find out the level of knowledge in using over the counter medicine including free and limited for self medication of society in RW 08, Morobangun, Jogotirto, Berbah, Sleman, Yogyakarta. This study belongs to descriptive observational to find out the subject characteristic, the level of knowledge and the description of the kind of medicine used by society of RW 08 Morobangun. The sample used in this study is the people who lived in Rw 08 Morobangun, Jogotirto, Berbah, Sleman, Yogyakarta. The data was taken from the interview with the patient by using the questionnaire. The sample collecting technique was nonrandom sampling and the method was accidental sampling with the number of the respondents were 175. The result showed that 175 respondents in RW 08 Morobangun, Jogotirto, Berbah, Sleman, Yogyakarta used self medication of over the counter medicine including free and limited only for their ailment. The level of knowledge in using over the counter medicine including free and limited for self medication of society in RW 08 Morobangun, Jogotirto, Berbah, Sleman, Yogyakarta showed that 42.9% reached the good category and 57,1% reached the sufficient category of 175 respondents. The conclusion of this study is the level of knowledge in using over the counter medicine including free and limited for self medication of society in RW 08 showed that most of the respondents achieved the sufficient category with 100 respondents (57,1%).